Movement of the patient and the cone beam computed tomography scanner: objectives and possible solutions - Hanzelka, Tomas; Dusek, Jaroslav; Ocasek, Filip; Kucera, Josef; Sedy, Jiri; Benes, Jiri; Pavlikova, Gabriela; Foltan, Rene (Oral surgery, oral medicine, oral pathology and oral radiology, 2013)
OBJECTIVE: This study aimed (1) to determine whether scanner arm rotation causes significant movement of the head restraint and (2) to measure patient movement and its variation during the scan. STUDY DESIGN: The iCAT scanner and a high-speed camera were used. The 40 patients were divided into 2 groups: the open-eyed group and the blindfolded group. RESULTS: The mean level of head restraint movement was 0.130 mm, with a significantly higher level at the beginning, probably owing to the accelerating arm. Mean movement of patients was 1.135 mm and 1.119 mm in the open-eyed and blindfolded groups, respectively. Patient movement was also significantly higher at the beginning of the scan, when noise and vibrations are likely to surprise the patient. CONCLUSIONS: Patient instruction and a dry-run scan should be done by clinicians. Manufacturers should consider separating the seat and head restraint from the rest of the scanner to avoid vibration transfer.
Keywords: Noise; vibrace; Restraint, Physical; Video Recording; Vision, Ocular; artefakty; pohyb; Prospective Studies; audiovizuální záznam; fyzické omezení; zrak; Vibration; lidé; Humans; Movement; počítačová tomografie s kuželovým svazkem; Artifacts; Cone-Beam Computed Tomography; hluk; prospektivní studie